THE EARNINGS MANAGEMENT IN ISLAMIC PERSPECTIVE - Trie Nadilla (IAIN Lhokseumawe, 2022)
As the business world evolves, every entity must be able to compete with the company's products in their own business fields. The quantity of profit obtained is one of the measuring instruments that may be used to measure the company's performance. The quantity of profit obtained is one of the measuring instruments that may be used to measure the company's performance. Profit management appears to have established a global business culture practiced by all companies. Although profit management practice theory is still regarded lawful when it does not conflict with Generally Accepted Accounting Principles (GAAP), but if viewed from Islamic business ethics then the practice of profit management is a practice that is considered not in line with the values contained in Islamic business ethics. Keyword : earning management; financial statement; Islamic perspective.